Rampant Lechers, Chaste Heroes. (De-)Sexualised Violence in Comic book Screen Adaptations Rampant Lechers, Chaste Heroes - Theresia Heimerl (Journal for Religion, Film and Media, 2017)
Violence is a central element of comic book screen adaptations in both Hollywood (Marvel, DC) and Japan. Yet while sexual violence is openly shown in film versions of manga, coded sexualised violence dominates Western productions. Positively connoted protagonists exercise violence, but no sexualised or sexual violence, in both groups. Conversely, villains are characterised by violence and some form of sexually grounded violence, but in Western films, they are ultimately repressed lechers, and only in Japanese productions do they rampantly lose their inhibitory control. Moreover,the heroes of Japanese films are noticeably less chaste than the almost asceticcelibate romantics of Marvel and DC.